2020
DOI: 10.1371/journal.pone.0243022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety towards COVID-19 and its associated factors among healthcare workers in a Hospital of Ethiopia

Abstract: Background The World Health Organization declared the outbreak of COVID-19 as a pandemic on 11 March 2020. Healthcare workers are directly involved in the prevention, diagnosis, treatment, and care of patients with COVID-19.This study aims to assess the prevalence of anxiety and its associated factors towards the COVID-19 outbreak among healthcare workers in a Hospital of Ethiopia. Methods A Hospital-based survey study was conducted on a total of 305 Healthcare workers in a Hospital of Ethiopia. Bivariable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
3
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 25 publications
6
59
3
12
Order By: Relevance
“…In a highly burdened area of northeastern Italy, a study showed that 50.1% of healthcare workers showed anxiety symptoms and 26.6% had moderate depressive symptoms (15). The incidences of anxiety and depressive symptoms among clinical doctors in our study were lower than those in previous studies (12,14,15). The possible reasons for these differences were as follows: first, the Chinese government had taken prompt and effective measures to enhance the sense of security of its citizens and to release frequent information on the epidemic.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In a highly burdened area of northeastern Italy, a study showed that 50.1% of healthcare workers showed anxiety symptoms and 26.6% had moderate depressive symptoms (15). The incidences of anxiety and depressive symptoms among clinical doctors in our study were lower than those in previous studies (12,14,15). The possible reasons for these differences were as follows: first, the Chinese government had taken prompt and effective measures to enhance the sense of security of its citizens and to release frequent information on the epidemic.…”
Section: Discussioncontrasting
confidence: 79%
“…In this study, we found that the incidence of anxiety and depressive symptoms among clinical doctors was approximately 11.1 and 16.90%, respectively, which was lower than that of previous studies conducted in other countries (12,14,15). Furthermore, we found that female doctors and those who have a minor child were associated with an increased risk of anxiety and depressive symptoms.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Ethiopia reported 152,806 confirmed cases, and 2279 deaths [ 5 ]. COVID-19 cases may be understated due to the lack of adequate diagnostic resources to test a larger number of people and a flimsy health care system in low-income countries [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study reflects no PPE access (OR 0.43; 95% CI, 0.20-0.90) to be statistically significant with anxiety which is found similar with the study (OR, 2.55; 95% CI, 1.43, 4.56). (16)…”
Section: Depressionmentioning
confidence: 99%